Checklist of Molluscs (Gastropoda and Bivalvia) of Malaysia Exclusive Economic Zone (EEZ) in Sarawak Waters - Jayasri, Ponnusami; Fazimah, Aziz (Universiti Malaysia Sarawak (UNIMAS), 2017)
Most of the molluscs studies in Malaysia have focused only on their diversity and the knowledge on their relationship with the water depth are lacking. The hypothesis tested in this research was water depth influence the density of marine gastropods and bivalves of Malaysia Exclusive Economic Zone (EEZ) in Sarawak waters. The aim of the study was to determine the gastropod and bivalve species in Malaysia EEZ of Sarawak waters and the relationship of the species density with water depth. The sampling was conducted from 15th August 2015 until 9th October 2015. The gastropods and bivalves were collected from 32 stations of various depths using the Smith-McIntyre grab. The depth of the stations was from 20 m to 200 m. A total of 95 taxa (61 Gastropoda and 34 Bivalvia) were found in this study. The dominant molluscs species of Sarawak waters in Malaysia EEZ were Limopsis sp., Turitella cingulifera, Pitar citrinus, and Cavolinia globulosa. Species density was about 10 ind./m2 to 610 ind./m2 and the total density was between 250 ind./m2 (Station 22) and 1,940 ind./m2 (Station 2). The total density of gastropods and bivalves showed weak correlation and negative relationship with the depth of water. The findings of this study will aid future studies in Malaysia EEZ.